Visual and Refractive Outcomes of Cataract Surgeries Performed in One Year in a Private Practice Setting: Review of 2714 Procedures - Laureano A. Rementería-Capelo; Jorge L. García-Pérez; Juan Gros-Otero; Aida Morán; José M. Sánchez-Pina; Inés Contreras (Journal of Ophthalmology)
Introduction. Currently available outcome data for cataract surgery include mostly patients from public health systems. The purpose of this study was to report the visual and refractive outcomes of cataract procedures performed during one year in a private practice center, which may include a different spectrum of patients. Methods. Our center’s database was used to identify all isolated cataract procedures performed during 2017. The electronic records were reviewed to collect the preoperative information, presence of intra- or postsurgical complications, and visual and refractive outcomes one month after surgery. Results. In 2017, 2714 eyes of 1543 patients underwent cataract surgery in our center. Mean patient age was 70.42 years. 775 eyes (28.55%) had prior ophthalmic pathologies, and 113 eyes (4.16%) had undergone previous surgical procedures. Surgical complications developed in 35 eyes (1.29%), including 9 posterior capsule tears (0.33%) and 3 cases of dropped lens fragments (0.11%). A toric or multifocal intraocular lens was implanted in 45.6% of eyes. As regards postoperative complications, 59 eyes (2.17%) required a return to the operating theater, including 29 eyes (1.07%) requiring reinterventions due to an unexpected refractive result. There were no cases of endophthalmitis. Mean LogMAR-corrected distance visual acuity (CDVA) improved from 0.25 (SD 0.34) preoperatively to 0.04 (SD 0.17) postoperatively; 86.5% of eyes achieved a CDVA ≤0.0, with 97.5% achieving ≤0.3. In 86.4% of eyes, the difference between target and residual spherical equivalent difference was of 0.50 D or lower; 88% of eyes had a spherical equivalent ±0.50 D. Conclusions. The visual and refractive outcomes of cataract surgery in a private practice setting were excellent, well over the benchmarks set by the ESCRS. The safety profile was also within expected standards. This study provides information for ophthalmologists in private practice on expected outcomes.